The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/cne.903290109
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of octopamine‐immunoreactive neurons in the central nervous system of the lobster

Abstract: It has been suggested that serotonin and octopamine serve important roles in behavioral regulation in lobsters. In this paper the locations of octopamine-immunoreactive neurons were mapped in wholemount preparations of the ventral nerve cord of 4th stage lobster (Homarus americanus) larvae. Approximately 86 neurons were found, distributed as follows: brain, 12; circumesophageal ganglia, 2; subesophageal ganglion, 38; thoracic ganglia, 6 each; and 4th and 5th abdominal ganglia, 2 each. All the octopamine-immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 34 publications
4
65
0
Order By: Relevance
“…To test the specificity of the antibody, we preincubated the antiserum (1:1,000) with 5 × 10 −3 M DL-octopamine from Sigma at 4°C for 24 hours (Schneider et al, 1993). Control larval CNSs were then incubated with preabsorbed primary antibody and were processed as described above.…”
Section: Body Wall Musclesmentioning
confidence: 99%
See 3 more Smart Citations
“…To test the specificity of the antibody, we preincubated the antiserum (1:1,000) with 5 × 10 −3 M DL-octopamine from Sigma at 4°C for 24 hours (Schneider et al, 1993). Control larval CNSs were then incubated with preabsorbed primary antibody and were processed as described above.…”
Section: Body Wall Musclesmentioning
confidence: 99%
“…Certain octopaminergic DUM neurons have also been revealed by the sulphide silver-staining method, which detects endogenous copper, a cofactor of the octopamine biosynthetic enzyme tyramine β-hydroxylase (Siegler et al, 1991). Recently, antibodies highly specific to octopamine have been developed that facilitate more definitive mapping of octopaminergic neurons in the nervous systems of several animals (Konings et al, 1988;Eckert et al, 1992;Stevenson et al, 1992;Schneider et al, 1993).In Drosophila melanogaster, there is good evidence that the amines octopamine, 5-HT, and dopamine are utilized in the nervous system (reviewed by Restifo and White, 1990). For example, electrophysiological studies suggest effects of octopamine on the adult neuromuscular junction (Dudai et al, 1987).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…FMRFamide-related peptides-The Drosophila FMRFamide gene encodes as many as 15 neuropeptides (Nambu et al, 1988) which are synthesized, and potentially secreted into the hemolymph from neurosecretory organs localized in the dorsal region of the CNS, but not from nerve terminals at the NMJ (Schneider et al, 1993). Assay of a large group of these peptides at the NMJ showed that they had essentially redundant functionality, enhancing twitch tension presumably by increasing EJC amplitude (Hewes et al, 1998).…”
Section: Peptides and Secreted Proteinsmentioning
confidence: 99%